THE URGENCY OF ASSET FORFEITURE LEGISLATION: OPTIMIZING THE PREVENTION OF CORRUPTION CRIMES - Santoso, Hardi Anugrah (ANAYASA : Journal of Legal Studies, 2025)
To create a nation that is free and clean from corruption, the government has made various efforts, including by establishing the Corruption Eradication Commission (KPK). Thus, other instruments also need to be reviewed on the effectiveness of corruption eradication in Indonesia. The existence of this study aims to urge the ratification of the Asset Forfeiture Bill which can be an optimal tool in preventing corruption crimes. This research uses normative legal research methods, which are research that focuses on the study of written legal norms, such as laws, draft laws, regulations, and other legal documents. The analysis was carried out qualitatively to interpret, understand, and evaluate legal norms related to asset confiscation in the eradication of corruption in Indonesia. The results of the study show that there are consequences that have great potential to minimize the crime of corruption. Among them is a deterrent effect which will affect the psychological state for perpetrators of corruption crimes and narrow the space for misuse of the state budget which has the potential to have an impact on the loss of personal assets of the perpetrators.